FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PERUSAHAAN PADA PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS - Michelle Patricia Citra; Yanti Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This research plans to figure out how the representation of liquidity, leverage, firm size, dan working capital turnover on company performance in the consumer noncyclicals sector listed on the Indonesia Stock Exchange during 2018-2021 period. Sample was selected using purposive sampling method and should be able to fulfill the criteria which is 30 companies. Data processing techniques using multiple regression analysis and Wilcoxon signed rank test with Microsoft Excel 365 and SPSS (Statistical Product and Service Solution) program. The results of this research indicate that firm size does have a significant influence on firm perfomance, while liquidity, leverage, and working capital turnover does not have a a significant influence on firm performance in the pre pandemic. Meanwhile the results also indicate that leverage, size, and working capital does have a significant influence on firm perfomance, while liquidity does not have a a significant influence on firm performance in the during pandemic. In addition, there isn’t any difference between the average firm performance before and during the COVID-19 pandemic.